Study protocol: understanding pain after dental procedures, an observational study within the National Dental PBRN - Elisabeth Kalenderian; Joel White; Alfa-Ibrahim Yansane; Janelle Urata; David Holmes; Kimberly Funkhouser; Rahma Mungia; Jin Xiao; Cindy Rauschenberger; Ana Ibarra-Noriega; Duong Tran; D. Brad Rindal; et al. (BMC Oral Health, 2022)
Abstract Background Patient-reported outcome measures provide an essential perspective on the quality of health care provided. However, how data are collected, how providers value and make sense of the data, and, ultimately, use the data to create meaningful impact all influence the success of using patient-reported outcomes. Objectives The primary objective is to assess post-operative pain experiences by dental procedure type through 21 days post-procedure as reported by patients following dental procedures and assess patients’ satisfaction with pain management following dental surgical procedures. Secondary objectives are to: 1) assess post-operative pain management strategies 1 week following dental surgical procedures, as recommended by practitioners and reported by patients, and 2) evaluate practitioner and patient acceptance of the FollowApp.Care post visit patient monitoring technology (FollowApp.Care). We will evaluate FollowApp.Care usage, perceived usefulness, ease of use, and impact on clinical workload. Design and methods We describe the protocol for an observational study involving the use of the FollowApp.Care platform, an innovative mobile application that collects dental patients’ assessments of their post-operative symptoms (e.g., pain). The study will be conducted in collaboration with the National Dental Practice-based Research Network, a collective Network of dental practices that include private and group practices, public health clinics, community health centers and Federal Qualified Health Centers, academic institutional settings, and special patient populations. We will recruit a minimum of 150 and up to 215 dental providers and up to 3147 patients who will receive push notifications through text messages FollowApp.Care on their mobile phones at designated time intervals following dental procedures. This innovative approach of implementing an existing and tested mobile health system technology into the real-world dental office setting will actively track pain and other complications following dental procedures. Through patients’ use of their mobile phones, we expect to promptly and precisely identify specific pain levels and other issues after surgical dental procedures. The study’s primary outcome will be the patients’ reported pain experiences. Secondary outcomes include pain management strategies and medications implemented by the patient and provider and perceptions of usefulness and ease of use by patients and providers.